Reconfigurations des formes canoniques du discours rapporté en milieu numérique : quelques exemples remarquables de discours directs - Laurence ROSIER (E-REA)
This paper follows previous research with Francis Grossmann (Grossmann and Rosier 2016), focusing on the reshaping of forms of “pre-digital” reported speeches in the age of technoforms; it shows the necessity to combine “traditional” linguistic descriptions with techno-conceptions of forms of reported speech. The different uses of social media are intrinsically linked to the circulation of speeches, which can be regarded as an anthropological dimension of communication. The evolution of the use of reported speech as a shared discourse coincides with the original forms of reported speech that are recombined and augmented by hyperlinks with multiple functions. The actions of quoting, sharing and commenting add a polemical dimension to reporting and circulating practices. This means that there is a major change on the institutionalisation and endorsement of circulating discourse, which is undermined as all discourses can normally circulate similarly. Every utterance therefore needs to be validated by various circulations and re-enactments.